Psychological competence of social workers in the context of war: the need for training and retraining of professionals - Nesterenko, Daria (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2024)
The article examines the need to improve the psychological competence of social workers in the context of working with vulnerable groups in the context of a full-scale invasion and its consequences for the mental health of the population. The relevance of the study is due to the growing number of people with psychological problems, including post-traumatic stress disorders (PTSD), depression and anxiety, which requires new skills for social workers to work with traumatized clients. The purpose of the article is to substantiate the need to improve psychological competence as a component of the training and retraining of social workers. The research methodology is based on the analysis of statistical data, scientific literature and the results of an empirical study conducted by the author through in-depth interviews with current professionals. The results of the study confirm that social workers face significant emotional stress, which leads to the risk of professional burnout. To work effectively with vulnerable populations, such as military personnel, veterans, internally displaced persons, and children, it is necessary to develop psychological competence, including self-regulation and trauma management skills. The scope of the research results includes educational programs for future social workers, as well as professional development programs for existing professionals. The authors propose the introduction of specialized courses, trainings, supervision, and mentoring programs aimed at developing psychological skills and supporting the emotional state of employees. The conclusions of the article emphasize the strategic importance of improving the psychological competence of social workers to improve the quality of social services and stabilize the socio-psychological state of society.